(untitled) (The Pakistan Development Review, 2025)
This paper aims to develop a composite Inclusive Growth Index (IGI) for 36 districts of Punjab, incorporating six overarching dimensions including (i) economic, (ii) amenities, (iii) gender equity and financial inclusion, (iv) human development (v) governance and (vi) sustainability. Following the OECD’s Handbook of Composite Indices, the study uses a minmax approach for the normalisation of indicators followed by the weighted aggregation using Principal Component Analysis (PCA) for assigning weights to indicators in each dimension in the composite index. The study ranks the districts as out-performing, average-performing, and lagging districts in terms of social inclusion. According to the ranking, the central and northern districts of Punjab such as Lahore, Gujrat, and Rawalpindi, etc. are scoring high on IGI, while districts falling in South Punjab such as Rajanpur, Dera Ghazi Khan, and Muzaffargarh, etc. are lagging. The result of the study highlights the areas and dimensions of social inclusion where the districts are lacking and, consequently, the policymakers and planners need to focus on these.